ACHIEVING COMPETITIVE POSITIONING: THE ROLE OF KNOWLEDGE CREATION AND QUALITY IN MANAGEMENT CONSULTANT-CLIENT COLLABORATION - Khanna, Rohan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study investigates the critical components that contribute to the success of management consulting partnerships and their role in driving client firms’ competitiveness. Using a descriptive research design, this study collected survey data from 402 senior executives from client companies in India with prior experience in management consulting. Data analysis was performed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) to assess the relationships between critical success factors and client outcomes. This study reveals that the successful implementation of critical success factors positively impacts firm qualities, and knowledge creation, all of which contribute to enhanced business positioning. Notably, knowledge creation followed by qualities was found to be a significant driver of competitive advantage, supporting the strategic importance of leveraging insights generated through consulting engagements. This research contributes to the literature by offering a deeper understanding of how management consulting partnerships can be leveraged for sustained competitive success.